Legal pluralism, indigenous law and legal coloniality: Thinking the right from the coloniality of power - Garzón López, Pedro (2019)
This article presents an outline of the “legal coloniality” following some theoretical lines of Latin American decolonial thought in order to analyze the limits of legal pluralism in the context of the current colonial States. In this regard, we use indigenous law as an analytical model to try to explain the difficulty of achieving an equitable relationship between two different legal systems which coexist in a context of colonial subordination. Questioning the state law beyond the law implies revealing the coloniality of power that underlies the modern trilogy and the foundation of legal monism: State/sovereignty/law.